EFEKTIVITAS PENGGUNAAN MEDIA BENDA KONGKRET UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Muhammad Supian Sauri; Novi Nurdian (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2025)
This research aims to evaluate the effectiveness of using concrete object media in improving student learning outcomes at SD Negeri Alalak Selatan 4 Banjarmasin. The research was conducted in class V and used pre-test and post-test techniques to collect data. The test is given in the form of essay questions that cover integer arithmetic operations. The research results show that there is no significant influence from the use of concrete object media on student learning outcomes. Although there was an increase in learning outcomes after treatment with this media, the difference was not significant. Statistical analysis using the t-test shows that the tcount value is smaller than the ttable value, so the hypothesis is rejected. In conclusion, the use of concrete object media has not had a significant impact on student learning outcomes due to the possibility of students' lack of habits and skills in using this media.